2020
DOI: 10.1371/journal.pone.0230519
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of Constitutive and fiber-specific promoters under the expression pattern of Expansin gene in transgenic Cotton

Abstract: Promoters are specified segments of DNA that lead to the initiation of transcription of a specific gene. The designing of a gene cassette for plant transformation is significantly dependent upon the specificity of a promoter. Constitutive Cauliflower mosaic virus promoter, CaMV35S, due to its developmental role, is the most commonly used promoter in plant transformation. While Gossypium hirsutum (Gh) being fiber-specific promoter (GhSCFP) specifically activates transcription in seed coat and fiber associated g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
(40 reference statements)
1
4
0
Order By: Relevance
“…We compared the information obtained from metaphase FISH (Mahmood-ur-Rahman et al, 2012;Latif et al, 2015;Ali et al, 2016) to better explain the phenomenon of position effect and effect of transgene copy number. Our results are very similar to already published data (Rao et al, 2013;Ali et al, 2016;Yaqoob et al, 2020) and confirm the idea of copy number variation. There are lots of techniques which are developed to visualize the single copy of foreign DNA in plant species.…”
Section: Figure-5: Fish Analysis Of Transgenic Pollen To Study Copy Number and Position Of Cry1ac Genesupporting
confidence: 93%
“…We compared the information obtained from metaphase FISH (Mahmood-ur-Rahman et al, 2012;Latif et al, 2015;Ali et al, 2016) to better explain the phenomenon of position effect and effect of transgene copy number. Our results are very similar to already published data (Rao et al, 2013;Ali et al, 2016;Yaqoob et al, 2020) and confirm the idea of copy number variation. There are lots of techniques which are developed to visualize the single copy of foreign DNA in plant species.…”
Section: Figure-5: Fish Analysis Of Transgenic Pollen To Study Copy Number and Position Of Cry1ac Genesupporting
confidence: 93%
“…Different plant expression vectors are used for plant transformation under efficient promoters. Promoter is a specified Segment of DNA that initiates a transcription of a specific gene (Yaqoob et al, 2020). Promoters are selected or designed based on the expression of the required gene.…”
Section: Discussionmentioning
confidence: 99%
“…This has been proved through various studies that revealed the relative expression of the tissue specific and constitutive promoters. The level of expression of the gene in cotton plant indicates the difference between constitutive and tissue specific promoter (Yaqoob et al, 2020). The introduction of gene for overexpression in cotton using CaMV35S promoter causes visible differences in plant phenotypes such as plant height, boll number, boll weight, fiber strength and length .…”
Section: Discussionmentioning
confidence: 99%
“…Very recently, several studies have been conducted to detect foreign genes by using FISH e.g. CRSP-1 and CRSP-2 (Ali et al, 2016), phytochrome B gene (Rao et al, 2013) and CpEXPA1 gene (Yaqoob et al, 2020) in cotton.…”
Section: Figure-2: Metaphase Chromosome Preparation Of Cotton From Me...mentioning
confidence: 99%